METODE RGEC UNTUK MENILAI KINERJA KEUANGAN PT BANK PANIN SYARIAH, TBK PERIODE 2016-2019 - Roy Seleky; Meiske Wenno (Manis: Jurnal Manajemen dan Bisnis, 2021)
PT Bank Panin Dubai Syariah Tbk in 2019 recorded financing growth, but this was not comparable to the bank's profit achievement in that year. The purpose of writing this article is to analyze and evaluate the financial performance of PT Bank Panin Dubai Syariah, Tbk for the period 2016 – 2019 using the RGEC method. The data analysis method used in this study is a quantitative analysis method by calculating, analyzing and interpreting data describing NPF, FDR, GCG, ROA, NOM and CAR. The results of the calculation of the financial performance of PT Panin Bank Dubay Syariah in 2016-2019 are NPF in the "good" category with an average ratio of 3.91%, FDR in the "good enough" category with an average of 90.87%. GCG in 2016-2019 is ranked 2 which shows the bank is in the "good" category. Panin Dubai Syariah bank ROA results for 2016 - 2019, banks are in the "not good" category because they have an average of -2.63%. Panin Dubai Syariah NOM results for 2016 - 2019, banks are in the "not good" category because they have an average of -24.35%. The results of the CAR of Panin Dubai Syariah bank in 2016 -2019, the bank is in the "very good" category because it has an average of 16.82%.